Difference between revisions of "2019 AIME I Problems/Problem 8"
(→Solution) |
Emathmaster (talk | contribs) (→Solution(BASH)) |
||
Line 3: | Line 3: | ||
==Problem 8== | ==Problem 8== | ||
==Solution(BASH)== | ==Solution(BASH)== | ||
− | Remember <math>sin^2(x)+cos^2(x)=1</math>. This means <math>sin^{10}(x)+cos^{10}(x)=(sin^2(x)+cos^2(x))sin^{10}(x)+(sin^2(x)+cos^2(x))cos^{10})(x)=sin^{12}(x)+cos^{12}(x)+sin^2(x)cos^{10}(x)+sin^{10}(x)cos^{2}(x)=sin^{12}(x)+cos^{12}(x)+sin^2(x)cos^{2}(x)[sin^8(x)+cos^8(x)]</math>. Let us look at | + | Remember <math>sin^2(x)+cos^2(x)=1</math>. This means <math>sin^{10}(x)+cos^{10}(x)=(sin^2(x)+cos^2(x))sin^{10}(x)+(sin^2(x)+cos^2(x))cos^{10})(x)=sin^{12}(x)+cos^{12}(x)+sin^2(x)cos^{10}(x)+sin^{10}(x)cos^{2}(x)=sin^{12}(x)+cos^{12}(x)+sin^2(x)cos^{2}(x)[sin^8(x)+cos^8(x)]</math>. Let us look at <math>sin^8(x)+cos^8(x)=(sin^2(x)+cos^2(x))sin^{8}(x)+(sin^2(x)+cos^2(x))cos^{8})(x)=sin^{10}(x)+cos^{10})(x) |
+ | |||
+ | ==Solution 2 (Another BASH)== | ||
+ | First, for simplicity, let </math>a=\sin{x}<math> and </math>b=\cos{x}<math>. Note that </math>a^2+b^2=1<math>. We then bash the rest of the problem out. Take the tenth power of this expression and get </math>a^{10}+b^{10}+5a^2b^2(a^6+b^6)+10a^4b^4(a^2+b^2)=\frac{11}{36}+5a^2b^2(a^6+b^6)+10a^4b^4=1<math>. Note that we also have </math>\frac{11}/{36}=a^{10}+b^{10}=(a^{10}+b^{10})(a^2+b^2)=a^{12}+b^{12}+a^2b^2(a^8+b^8)<math>. So, it suffices to compute </math>a^2b^2(a^8+b^8)<math>. Let </math>y=a^2b^2<math>. We have from cubing </math>a^2+b^2=1<math> that </math>a^6+b^6+3a^2b^2(a^2+b^2)=1<math> or </math>a^6+b^6=1-3y<math>. Next, using </math>\frac{11}{36}+5a^2b^2(a^6+b^6)+10a^4b^4=1<math>, we get </math>a^2b^2(a^6+b^6)+2a^4b^4=\frac{5}{36}<math> or </math>y(1-3y)+2y^2=y-y^2=\frac{5}{36}<math>. Solving gives </math>y=1<math> or </math>y=\frac{1}{6}<math>. Clearly </math>y=1<math> is extraneous, so </math>y=\frac{1}{6}<math>. Now note that </math>a^4+b^4=(a^2+b^2)-2a^2b^2=\frac{2}{3}<math>, and </math>a^8+b^8=(a^4+b^4)^2-2a^4b^4=\frac{4}{9}-\frac{1}{18}=\frac{7}{18}<math>. Thus we finally get </math>a^{12}+b^{12}=\frac{11}{36}-\frac{7}{18}*\frac{1}{6}=\frac{13}{54}<math>, giving </math>\boxed{067}$. | ||
==See Also== | ==See Also== | ||
{{AIME box|year=2019|n=I|num-b=7|num-a=9}} | {{AIME box|year=2019|n=I|num-b=7|num-a=9}} | ||
{{MAA Notice}} | {{MAA Notice}} |
Revision as of 19:16, 14 March 2019
The 2019 AIME I takes place on March 13, 2019.
Problem 8
Solution(BASH)
Remember . This means . Let us look at $sin^8(x)+cos^8(x)=(sin^2(x)+cos^2(x))sin^{8}(x)+(sin^2(x)+cos^2(x))cos^{8})(x)=sin^{10}(x)+cos^{10})(x)
==Solution 2 (Another BASH)== First, for simplicity, let$ (Error compiling LaTeX. Unknown error_msg)a=\sin{x}b=\cos{x}a^2+b^2=1a^{10}+b^{10}+5a^2b^2(a^6+b^6)+10a^4b^4(a^2+b^2)=\frac{11}{36}+5a^2b^2(a^6+b^6)+10a^4b^4=1\frac{11}/{36}=a^{10}+b^{10}=(a^{10}+b^{10})(a^2+b^2)=a^{12}+b^{12}+a^2b^2(a^8+b^8)a^2b^2(a^8+b^8)y=a^2b^2a^2+b^2=1a^6+b^6+3a^2b^2(a^2+b^2)=1a^6+b^6=1-3y\frac{11}{36}+5a^2b^2(a^6+b^6)+10a^4b^4=1a^2b^2(a^6+b^6)+2a^4b^4=\frac{5}{36}y(1-3y)+2y^2=y-y^2=\frac{5}{36}y=1y=\frac{1}{6}y=1y=\frac{1}{6}a^4+b^4=(a^2+b^2)-2a^2b^2=\frac{2}{3}a^8+b^8=(a^4+b^4)^2-2a^4b^4=\frac{4}{9}-\frac{1}{18}=\frac{7}{18}a^{12}+b^{12}=\frac{11}{36}-\frac{7}{18}*\frac{1}{6}=\frac{13}{54}\boxed{067}$.
See Also
2019 AIME I (Problems • Answer Key • Resources) | ||
Preceded by Problem 7 |
Followed by Problem 9 | |
1 • 2 • 3 • 4 • 5 • 6 • 7 • 8 • 9 • 10 • 11 • 12 • 13 • 14 • 15 | ||
All AIME Problems and Solutions |
The problems on this page are copyrighted by the Mathematical Association of America's American Mathematics Competitions.